Implementasi Manajemen Peserta Didik Berbasis Sekolah di Palembang - Bambang Irawan; Zainal Berlian (Program Magister Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2020)
The purpose of this study was to determine the implementation of management, supporting factors and inhibiting factors in SMP Palembang. This type of research is a naturalistic qualitative field research. Data sources were obtained from primary data and secondary data. Data collection techniques using observation, documentation, and interviews. Then the data were analyzed by means of reduction, data presentation and verification. Based on the results of data analysis, it is known that management implementation is going well because the scope of management of students studied, starting from student planning, acceptance, orientation, attendance, grouping, evaluation, increase, transfer (transfer), drop out (stop) , the code of ethics, punishment, and discipline have worked well. This is evident from the results of interviews, documentation and observations made by researchers. Even though there are deficiencies in terms of existing facilities and infrastructure, these deficiencies are running well because there are educators, employees, students, parents, government, supporting facilities and infrastructure, as well as the surrounding community who participates for the progress of the school